Rural Livelihood Resilience: An Assessment of Social, Economic, Environment, and Physical Dimensions - Rudiarto, Iwan; Handayani, Wiwandari; Wijaya, Holi B.; Insani, Tia D. (MATEC web of conferences, 2019)
Rural coastal area in northern part of Sayung subdistrict isprone to tidal flood as effect of abrasion and sea level rise. This studylooks at the condition of five villages that suffer the most tidal flood thereand tries to measure the livelihood resilience of the people throughhousehold survey. Livelihood Resilience Index (LRI) and Resilience Radarare adapted to calculate the score and level of livelihood resilience. Fourdimensions (social dimension, economic dimension, environmentdimension, and physical-infrastructure dimension) are used to express thelivelihood resilience score of each study area. Sriwulan village has thehighest score among the study areas and it has medium level of livelihoodresilience while Timbulsloko village which has the lowest score becomesthe only study area with low level livelihood resilience. However, thisresult in score and level categorization are only an attempt to describe thespectrum of livelihood resilience instead of intending to provide a set ofclassification. It hopefully can help to identify what can be started first inthe work of building resilience of the people and community in tidal floodproneareas.